The predictive role of temperamental traits and inhibitory-control skills on ego resiliency of preschool children [Mizaç özellikleri ve öz kontrol becerilerinin okul öncesi dönem çocuklardaki ego sağlamlık düzeyini yordayıcı rolü] - (:unkn) unknown (Ankara University, 2018)
Ego resiliency means positive development tendency despite risk factors. Resilient children are expected to cope with individual, familial and environmental risk factors, so developing resiliency could be accepted as a developmental task for children. The aim of the study is to investigate the predictive role of two selected individual variables; inhibitory control skills and temperament characteristics of preschool children, on their ego resiliency levels. The study is in survey method. The sample of the study includes 55-73 months old 78 children, who attend preschools. The data collection tools that are used in this study are; The Personal Information Form, The Short Temperament Scale for Children and Children’s Ego Resiliency Scale (Mother Form). Also two tasks, named as Green-Red Signs and Touch Your Toe were used to assess preschoolers’ inhibitory control skills. When all the variables are considered together in the regression analysis, it has been found that the inhibitory control skills are significantly predictive of children's ego resiliency, but temperamental characteristics are not. © 2019, Ankara University. All rights reserved.
Keywords: Ego resiliency; Inhibitory control; Preschool children; Temperament